PENGEMBANGAN BAHAN PERPUSTAKAAN PADA PERPUSTAKAAN OMBUDSMAN REPUBLIK INDONESIA: STUDI KASUS - Damaji Ratmono (Maktabatuna, 2020)
The Ombudsman Library of the Republic of Indonesia, which is part of a special library in nonstructural state institutions, has concepts, strategies, and policies in library materials development activities. This paper describes some of the concepts or strategies adopted by the Ombudsman library in developing its library materials. The purpose of this paper is that readers, especially library managers, can increase their insight and knowledge about the Ombudsman library and know the concept of the Indonesian Ombudsman library in developing library materials so that it is hoped that these concepts and strategies can be input by library managers and can meet the satisfaction of visitors who use the Ombudsman library in in terms of collection availability. The method used in this writing is through observation (Field Research), Interview (Interview), and literature study. From the results of the discussion it is known that the Ombudsman library in developing its library materials applies concepts and strategies, namely first through the purchase / acquisition of library materials with a planned budget every year. The second concept is through gifts or grants from libraries and libraries from State institutions. The third concept is through a deposit or repository, by issuing a regulation or Circular of the Chairman of the Ombudsman concerning the Obligation to Save Printed and Recorded Works, and the fourth is through the exchange of collections. With the existing concepts, strategies, and policies in the Indonesian Ombudsman library, it is hoped that collection development activities will continue for the sake of creating service satisfaction to users in the Indonesian Ombudsman environment and for the general public.